The effect of trapping on Arctic Foxes in Svalbard : demography and genetics - Meldrum, Elaine Alice (Universitetet i Tromsø, 2012)
For hundreds of years arctic foxes on the Svalbard archipelago have been hunted and trapped for their warm and attractive fur. However, little is known about the effect that trapping has on this species population structure. Here I assess the effect of trapping on arctic foxes by comparing the demographic and genetic structure of foxes from the Austfjordnes area in Svalbard over three consecutive hunting seasons. The investigation focusses on changes to the demographic makeup of age structure, sex ratio, female reproduction and body weight from a population that had been low to moderately harvested (2008 – 2009) to those which had been intensively harvested (2009 – 2010 and 2010 – 2011). I also address whether there is a significant change in genetic diversity between the 2008 – 2009 and 2009 – 2010 trapping seasons and test for genetic subdivision within the population. Analyses of age structure revealed a breakdown in the usual population structure by a significant decrease of reproductive adults (especially females) and higher numbers of juveniles in the trapping area. Trapping did not seem to significantly alter the sex ratio or the proportion of females reproducing. However, the lack of reproductive females over three years old would influence future population numbers. Changes to body weight were thought to be related to reproduction and the effects of weather. Genetic analyses showed an increase in allelic richness and significant genetic differentiation between trapping seasons suggesting high immigration rates into the area. Keywords: Hunting; Demography; Age structure; Sex Ratio; Reproduction; Body Weight; Genetics; Genetic diversity; Genetic subdivision.